THE INFLUENCE OF COGNITIVE BEHAVIOUR THERAPY TO DECREASE THE LEVEL OF DEPRESSION FOR LEPROSY SUFFERER - Ima Rahmawati; Enny Virda Yuniarti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Leprosy is the ill that caused by mycobacterium leprae bacteria, which caused complex problem for leprosy sufferer. It gives bad effect in some aspects such as physic, social, economy, and psychology. Psychologically, the leprosy sufferer gets the problem because of too much stigma to leprosy by society. Consequently, the leprosy sufferer stands aloof from the others, he feels shy, and gets depression. One of non-pharmacology treatment that can decrease the level of depression is Cognitive Behavior Therapy. Cognitive Behaviour Therapy, which is an approach with someone to recognize and to change the bad mindset or maladaptive. This present research is to reveal the influence of Cognitive Behaviour Therapy to decrease the level of depression for leprosy sufferer. The design of this present research is Pre-experiment with One Group Pre-Post Test Desaint approach. The 25 samples are taken by Consecutive Sampling. The data collection is collected by Beck Depression Inventory (BDI) questionnaire. Statistic test is used by Wilcoxon Signed Rank Test, which showed p (0,001) < Î±(0,05), with the result that H0 is rejected, it means there is an influence of Cognitive Behaviour Therapy to decrease the level of depression for leprosy sufferer. Most of the leprosy sufferer in a hospitalization leprosy service get lower depression. The sufferers often need psychology intervention to treat on depression. Cognitive Behaviour Therapy is psychology therapy that quiet simple because the key of CBT identifies the mindset, feel, and behavior, which mold reaction. Furthermore, the sufferers decide by their own ability whether the idea is rational and benefit for them